graded readers : adventures of huckleberry finn - Twain, Mark; Mark twain (New dawn press, 2005)
The Adventures of Huckleberry Finn follows Huck, a boy fleeing his abusive father, and Jim, a man escaping slavery, as they travel down the Mississippi River on a raft. They encounter various, often dangerous, adventures, highlighting themes of freedom, friendship, and moral growth, while Huck battles his society's pro-slavery views.